2021
DOI: 10.1136/neurintsurg-2021-017760
|View full text |Cite
|
Sign up to set email alerts
|

Addition of intracranial aspiration to balloon guide catheter does not improve outcomes in large vessel occlusion anterior circulation stent retriever based thrombectomy for acute stroke

Abstract: BackgroundBalloon guide catheter (BGC) in stent retriever based thrombectomy (BGC+SR) for patients with large vessel occlusion strokes (LVOS) improves outcomes. It is conceivable that the addition of a large bore distal access catheter (DAC) to BGC+SR leads to higher efficacy. We aimed to investigate whether the combined BGC+DAC+SR approach improves angiographic and clinical outcomes compared with BGC+SR alone for thrombectomy in anterior circulation LVOS.MethodsConsecutive patients with anterior circulation L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Second, unlike previous studies, the balloon guiding catheter (BGC) was only used in 4‰ of patients from the ANGEL-ACT registry, which might also lead to different results between our and previous studies. However, Blasco et al also found that first-line SR+CA had a longer procedure duration than first-line SR alone, although all patients enrolled in their study used BGC 23. Third, the experience and preference of the neurointerventionists for the first-line thrombectomy technique might also be another possible explanation.…”
Section: Discussionmentioning
confidence: 90%
“…Second, unlike previous studies, the balloon guiding catheter (BGC) was only used in 4‰ of patients from the ANGEL-ACT registry, which might also lead to different results between our and previous studies. However, Blasco et al also found that first-line SR+CA had a longer procedure duration than first-line SR alone, although all patients enrolled in their study used BGC 23. Third, the experience and preference of the neurointerventionists for the first-line thrombectomy technique might also be another possible explanation.…”
Section: Discussionmentioning
confidence: 90%
“…After removing duplicates and screening for the titles and abstracts, 63 papers remained for full text review from which we excluded 58 papers (overlapping population, n=2; wrong outcome or no outcome reported, n=41; review, n=4; combined technique only used as salvage, n=2; unable to extract data, n=2; other endpoints, n=4; other, n=1). Finally, we included five studies in our meta-analysis,17 18 26–28 which included four cohort studies and one randomized trial. The quality of all of the included articles was high.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, addition of distal aspiration catheters to BGC and SR thrombectomy did not result in higher rates of FPE or improved clinical outcomes. 38 In refractory occlusions of large vessels, a novel double-stent retriever technique has also been proposed. In this approach, standard stent retriever-based thrombectomy techniques are used, however, a second stent retriever is deployed either within or in parallel to the first stent and thrombectomy performed to retrieve the refractory clots.…”
Section: Discussionmentioning
confidence: 99%